Co-inoculação no sulco, volume de calda, horários de semeadura e cargas bacterianas na cultura da soja - Silva, Dionatas Rodrigues da (2020)
The biological nitrogen fixation is able to supply all needs for this nutrient in soybean crops, eliminating the use of nitrogen fertilizers. The search by sufficiency on nutritional support depends on the technique of co-inoculation in the furrow sown which consists of the use of bacteria Bradyrhizobium spp. and Azospirillum spp. with a syrup volume, with the proposes of being an alternative for the greater bacteria survival in the soil. However, the environmental influences can reduce survival due to the stress occurrence, decrease the soil population, reduce the root nodulation, and soybean grain yield. Thus, the objective of this research was to evaluate the responses of co-inoculation performed in the furrow sown on the yield components and soybean nodulation, as well as to evaluate the relation among the syrup volumes, temperature, soil moisture in the sowing, and the bacteria concentration. Three experiments were carried out in the experimental area belonging to the Crop Protection Department of the Federal University of Santa Maria. In the 1st and 2nd experiments, co-inoculation via the sowing furrow was evaluated with volumes of 25, 50, 75, and 100 L ha-1, at three different sowing times, 8, 13 and 18 hours, and two different witnesses, with peat co-inoculation in the seed and without addition of inoculants in the seed, this one presenting only the chemical treatment. In the 3th experiment, co-inoculation was evaluated with volumes of 25, 50, 75 L ha-1, with sowing at 9 and 15 hours and compared to two controls, one with co-inoculation in the seed and the other one only with chemical treatment. Under ideal environmental conditions for soybeans, co-inoculation via sowing furrow in the spray volumes between 25 and 50 L ha-1 was efficient for nodulation and grain yield regardless of sowing time, being an alternative to co-inoculation via seeds. The use of 8.2 million UFCs in syrup volumes did not change the nodulation and productivity aspects in soybean culture.